Internalisasi Nilai Kearifan Lokal Bugis dalam Budidaya Padi Sawah: Perspektif Akuntansi Sosial dan Lingkungan - Rika Rahma; Hasdiana Hasdiana; Mentari Sinar Lestari (Owner : Riset dan Jurnal Akuntansi, 2026)
Rice farming is a strategic sector in supporting national food security and is an integral part of the cultural identity of the Bugis people in South Sulawesi. Agricultural practices in this region are not only based on agronomic techniques, but are also laden with local wisdom values such as siri’ na pacce (self-esteem and solidarity), mappatabe (mutual respect), and mabbulo sipeppa (mutual cooperation). From an accounting perspective, these local wisdom values are reflected in social and environmental accounting practices, including non-monetary resource management, informal cost-sharing systems, and accountability to the community and nature. This study aims to: (1) identify Bugis local wisdom values still practiced in paddy rice cultivation; (2) analyze the internalization process of these values from social, cultural, environmental, and accounting perspectives; and (3) develop a conceptual model integrating local wisdom and social-environmental accounting in modern sustainable agricultural practices. Using a qualitative method with a phenomenological interpretive approach, data were collected through in-depth interviews with twelve informants comprising farmers, traditional leaders, and agricultural extension workers in Desa Mattunru-Tunrue, Kecamatan Cempa, Kabupaten Pinrang. Data were analyzed using the interactive model of Miles, Huberman, and Saldana (2014). Findings reveal that Bugis local wisdom values remain embedded in rice farming through collective labor systems, pre-planting rituals, and social norms governing land use, all of which reflect principles of social accountability and environmental stewardship. Internalization occurs through intergenerational transmission supported by community leaders and informal institutions. A conceptual model integrating local wisdom and social-environmental accounting into modern sustainable agriculture is proposed. This study contributes academically and practically to culturally-rooted agricultural accounting policy development.